A Question of Posture: Engaging the World with Justin Martyr, George Lindbeck and Hans Frei - Thompson, Geoff (Pacifica, 2000)
This essay explores the posture adopted towards the world by one ancient and two contemporary Christian writers: Justin Martyr, George Lindbeck and Hans Frei. They respectively represent what are designated as defensive, receptive, and reciprocal postures, postures which determine the extent to which, and the manner in which, these writers appropriate insights and knowledge from beyond the Christian tradition. The theology and, to a lesser extent, the cultural background of each approach are studied. The particular doctrinal locus in question is Christology. An assessment is made of the link made by each author between the place of Jesus Christ in their theological framework and the posture which they adopt towards the rest of the world. Using the approaches of Justin and Lindbeck as a foil, Frei's idiosyncratic work will be shown to demonstrate that a high level of reciprocity between the church and the rest of the world is compatible with an orthodox Christology.